KETERAMPILAN SEPAK SILA PADA PERMAINAN SEPAKTAKRAW MELALUI METODE DRILL BAGI ANAK TUNARUNGU - Iskhak - Iskandar (Universitas Negeri Padang, 2013)
This research is back-grounded by a problem on deaf children can not do sepak sila in sepaktakraw game cause of the teacher in learning sepaktakraw sport on sepak sila did not give basic technique repeatedly. To solve that problem, researcher do repairing of learning activity with giving sipak sila technique with using Drill Method. This research aims to prove the drill method can increase mastering sipak sila on the deaf children. The research used action research class design collaborated with colleagues (subject teacher and sport teacher). The subject of research is fifth class of SLBN Tanjung Pinang with four deaf students. Research took place on first cycle using drill method have increased in mastering sipak sila even though not yet all of component in sipak sila technique can mastered fluently. In first cycle AP can noted name of kick and practice not fluently. IF can note the name of kick but not fluently in practice the kick. BK can note the name of kick but undirected in kicking. SY can noted the name of kick but still aided in doing unperfect kick. In second cycle, using drill method technique intensively of sepak sila with increasing becoming four meeting, so the result became very good like AP could name the kick and to practice the kick becoming straight. SY could name of kick and do the kick but rather angle, target kick was fine. Based on the result, the conclusion of this research that drill method could increase mastering sepak sila on sepaktakraw game on deaf students. The suggestion on this research, to apply drill method in next learning in the same material and sport learning.